Longitudinal contrast in turbulence along a ∼ 19° S section in the Pacific and its consequences for biogeochemical fluxes - P. Bouruet-Aubertot; Y. Cuypers; A. Doglioli; M. Caffin; C. Yohia; A. de Verneil; A. Petrenko; D. Lefèvre; H. Le Goff; G. Rougier; M. Picheral; T. Moutin (Biogeosciences, 2018)
Microstructure measurements were performed along the OUTPACE longitudinal transect in the tropical Pacific (Moutin and Bonnet, 2015). Small-scale dynamics and turbulence in the first 800 m surface layer were characterized based on hydrographic and current measurements at fine vertical scale and turbulence measurements at centimeter scale using a vertical microstructure profiler. The possible impact of turbulence on biogeochemical budgets in the surface layer was also addressed in this region of increasing oligotrophy to the east. The dissipation rate of turbulent kinetic energy, ϵ, showed an interesting contrast along the longitudinal transect with stronger turbulence in the west, i.e., the Melanesian Archipelago, compared to the east, within the South Pacific Subtropical Gyre, with a variation of ϵ by a factor of 3 within [100–500 m]. The layer with enhanced turbulence decreased in vertical extent travelling eastward. This spatial pattern was correlated with the energy level of the internal wave field, higher in the west compared to the east. The difference in wave energy mostly resulted from enhanced wind power input into inertial motions in the west. Moreover, three long-duration stations were sampled along the cruise transect, each over three inertial periods. The analysis from the western long-duration station gave evidence of an energetic baroclinic near-inertial wave that was responsible for the enhanced ϵ, observed within a 50–250 m layer, with a value of 8×10-9<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="42pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="7ab3425fe6839fc6c9d3c2f71f932374"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-15-7485-2018-ie00001.svg" width="42pt" height="14pt" src="bg-15-7485-2018-ie00001.png"/></svg:svg> W kg−1, about 8 times larger than at the eastern long-duration stations. Averaged nitrate turbulent diffusive fluxes in a 100 m layer below the top of the nitracline were about twice larger west of 170∘ W due to the higher vertical diffusion coefficient. In the photic layer, the depth-averaged nitrate turbulent diffusive flux strongly decreased eastward, with an averaged value of 11 µmolm-2d-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="62pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="da616652040692bb628e11c98a455ad0"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-15-7485-2018-ie00002.svg" width="62pt" height="15pt" src="bg-15-7485-2018-ie00002.png"/></svg:svg> west of 170∘ W compared with the 3 µmolm-2d-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="62pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="640de40df36e813b435790306f198a58"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-15-7485-2018-ie00003.svg" width="62pt" height="15pt" src="bg-15-7485-2018-ie00003.png"/></svg:svg> averaged value east of 170∘ W. Contrastingly, phosphate turbulent diffusive fluxes were significantly larger in the photic layer. This input may have an important role in sustaining the development of N2-fixing organisms that were shown to be the main primary contributors to the biological pump in the area. The time–space intermittency of mixing events, intrinsic to turbulence, was underlined, but its consequences for micro-organisms would deserve a dedicated study.